1991
DOI: 10.1093/nar/19.19.5313
|View full text |Cite
|
Sign up to set email alerts
|

Alternative tertiary structure attenuates self-cleavage of the ribozyme in the satellite RNA of barley yellow dwarf virus

Abstract: A self-cleaving satellite RNA associated with barley yellow dwarf virus (sBYDV) contains a sequence predicted to form a secondary structure similar to catalytic RNA molecules (ribozymes) of the 'hammerhead' class (Miller et al., 1991, Virology 183, 711-720). However, this RNA differs from other naturally occurring hammerheads both in its very slow cleavage rate, and in some aspects of its structure. One striking structural difference is that an additional helix is predicted that may be part of an unusual pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 41 publications
2
59
0
Order By: Relevance
“…Amongst naturally occurring hammerhead ribozymes, the GUCt motif is prevailing (3), but the satellite RNAs of lucerne transient streak virus RNA (sLTSV) and of barley yellow dwarf virus (sBYDV) contain either a GUA4 (1), or an AUAt, respectively (27). The latter satellite is exceptional since it contains an alternative secondary structure that attenuates self-cleavage (28 (37)(38)(39)(40), indicating a reduced catalytic turnover and a less efficient formation of the ribozyme/substrate complex, although some had been shown to be effective in living cells.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst naturally occurring hammerhead ribozymes, the GUCt motif is prevailing (3), but the satellite RNAs of lucerne transient streak virus RNA (sLTSV) and of barley yellow dwarf virus (sBYDV) contain either a GUA4 (1), or an AUAt, respectively (27). The latter satellite is exceptional since it contains an alternative secondary structure that attenuates self-cleavage (28 (37)(38)(39)(40), indicating a reduced catalytic turnover and a less efficient formation of the ribozyme/substrate complex, although some had been shown to be effective in living cells.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty picomoles of RNA were dephosphorylated and 59 end-labeled with 33 P, using polynucleotide kinase and g-33 P-ATP (Dupont-NEN)+ The labeled RNA was purified on a 6% polyacrylamide, 7 M urea denaturing gel, and the full-length RNA band was eluted (Miller & Silver, 1991)+ The amount of recovered RNA was determined by liquid scintillation counting+ T1 and V1 nuclease probing were performed as described by Miller & Silver (1991) except the reaction buffer was the same buffer as in wheat germ extract translation reactions: 24 mM HEPES/KOH, pH 7+6, 2 mM MgCl 2 , 133 mM KAc, and 0+8 U/mL RNasin+ A T1 sequencing ladder was generated under denaturing conditions as described in Miller & Silver (1991)+ Structural probing with imidazole was performed in 40 mM NaCl, 1 mM EDTA, 10 mM MgCl 2 with 0, 0+4, 0+8, or 1+6 M imidazole for 15 h as described in Vlassov et al+ (1995)+ Probed products were separated on an 8% polyacrylamide, 7 M urea sequencing gel+ The gels were dried and exposed to PhosphorImager screens for 24 h and visualized by a STORM 840 PhosphorImager (Molecular Dynamics)+ Secondary structure prediction and multiple alignment The MFOLD program (Zuker, 1989) in the GCG software package (GCG, Madison, Wisconsin) was used to predict the secondary structure of the TE and all mutants+ The default parameters were used, with the exception of the temperature, which was set to 25 8C as our in vitro and in vivo translation reactions+ Multiple alignments were performed by using CLUSTAL W (Thompson et al+, 1994) …”
Section: Rna Secondary Structure Probingmentioning
confidence: 99%
“…For example, the transition between the native and autocatalytic conformers of peach latent mosaic viroid (PLMVd) is the rate-limiting step in ribozyme catalysis [30]. Similarly, additional sequences in helix II of the satellite RNA of barley yellow dwarf virus (sBYDV) form a thermodynamically favored pseudoknot that inhibits selfcleavage [12]. Mutations that disrupt the pseudoknot increase self-cleavage several hundred fold but cause the satellite RNA to replicate poorly, indicating that rapid RNA cleavage is not essential for (sBYDV) replication [31].…”
Section: Dlseuulonmentioning
confidence: 99%
“…Subtle primary, secondary and tertiary structure interactions oftt, n lead to large differences in the cleavage rates of a particular catalytic motif [2,[11][12][13]. In particular, we and others have shown that the hammerhead ribozyme cleavage rate is often substantially less for full-length substrate RNAs than for shorter substrates [14][15][16].…”
Section: Introductionmentioning
confidence: 99%